Clark between Hockey Boards. Memorandum by J. A. Palous, 1922 (Report on the Development of the Cinematographic Department) - Klimes, Ivan (Iluminace, 2014)
The thematic introduction to the following Memorandum of J. A. Palous recalls the circumstances of the creation of the document and interesting facts about the personality of Jan Arnold Palous.
Keywords: editor of Prager Presse; ice hockey pioneer; sports columnist and journalist; history and film; legislation; state and film; film workers